O poeta apeado / The dismounted poet - Holzhausen, Marlene (Revista de Letras, 2007)
1945 é um ano-marco para a história literária do século XX. Os grandes centros europeus, que tradicionalmente promoviam a difusão das mais novas tendências estéticas, estão literalmente arruinados no final do conflito mundial. À ruína econômica, política e social, aliam-se o aniquilamento e a dispersão das vanguardas pelos quatro cantos do mundo. Em busca do elo perdido, os poetas da Alemanha e da Suíça voltam o olhar para os princípios da arte concreta e das vanguardas literárias do início do século. Os termômetros brasileiros acusam, por essa mesma época, a necessidade de reverter o quadro pouco alentador de pais exótico, mas subdesenvolvido. A economia brasileira avançara significativamente na década de 40 e abre-se mais uma vez a perspectiva de acalentar o sonho de um “país do futuro”. É a chance tão esperada de galgar (dois a dois) os degraus rumo ao grupo seleto de países do primeiro mundo. Estes fatores propiciam promovem o surgimento de uma nova dicção poética na década de 1950: a poesia concreta na Alemanha, na Suíça e no Brasil que são objeto deste estudo. 1945 is konwn as a landmark for 20th century literary history. The great European centers, which traditionally promoted the interest in spreading the newet esthetic trends, are literally ruined at the end of World War II. Such na economical political and social ruin is worsened by the extermination and scattering to the four corners of earth of those standing in the literary forefront. Trying to find out the missing link, German and Swiss poets go back to the principles of Concrete Art and the literary avant-garde of the beginning of the century. Brazilian enlightened literary critics of that same period stress the nedd to straighten the country’s unattractive flaw as being exotic but undeveloped. The Brazilian economy made a significant progress in the 1940’s and once more the dream to become “the land of the future” is intensely fondled. Thst is the riht time to climb over the staricase every two satairsteps to attain a better ranking among the top countries of the world. Such elements favor and promote the arising of a new poetic expression in the 1950’s: concrete peotry. These are indees the literary antecedents which make way to the development of concrete poetry in Germany Switzerland and Brazil which is the subject at issue in this paper.